Peran Kantor Urusan Agama (KUA) dalam Meminimalisir Terjadinya Pernikahan Dini dimasa Pandemi Covid19 - Ach. Syah Khoirun Na’im; Muhyidin, Muhyidin; Sutopo, Sutopo (HOKI : Journal of Islamic Family Law, 2023)
As human life develops, problems arise in society, namely the frequent occurrence of marriages carried out by someone who is not yet old enough to get married, therefore the role of the KUA is needed in minimizing early marriage. The research method used in this research is a research method using a qualitative approach, where the research carried out is descriptive. The results of the analysis show that the increase in the number of early marriages during the Covid-19 period was caused by people who had minimal knowledge about the importance of minimum marriage limits and about the psychological and reproductive health impacts for someone who married early. The KUA has minimized early marriage by playing an administrative role and providing outreach to the community so that they are more enthusiastic about the importance of the minimum age limit for early marriage which is carried out evenly both in institutions and in villages in the sub-district.